2007
DOI: 10.1007/s00572-007-0124-7
|View full text |Cite
|
Sign up to set email alerts
|

Sporulation and diversity of arbuscular mycorrhizal fungi in Brazil Pine in the field and in the greenhouse

Abstract: The aim of this work was to assess the sporulation and diversity of arbuscular mycorrhizal fungi (AMF) at different forest sites with Araucaria angustifolia (Bert.) O. Ktze. (Brazil Pine). In addition, a greenhouse experiment was carried out to test the use of traditional trap plants (maize + peanut) or A. angustifolia to estimate the diversity of AMF at each site. Soil samples were taken in two State Parks at southwestern Brazil: Campos do Jordão (Parque Estadual de Campos do Jordão [PECJ]) and Apiaí (Parque … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
19

Year Published

2008
2008
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(44 citation statements)
references
References 23 publications
2
22
1
19
Order By: Relevance
“…Recently, Moreira et al (2007b) found a total of 25 taxa in a survey of three A. angustifolia ecosystems in the State of São Paulo. Also, in all the before-mentioned studies, Acaulospora and Glomus were the genera with the greatest number of species.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Moreira et al (2007b) found a total of 25 taxa in a survey of three A. angustifolia ecosystems in the State of São Paulo. Also, in all the before-mentioned studies, Acaulospora and Glomus were the genera with the greatest number of species.…”
Section: Resultsmentioning
confidence: 99%
“…When comparing a native forest with Araucaria and a reforested area with both Araucaria and Pinus in the State of São Paulo, Moreira-Souza et al (2003) found a greater number of AMF spores in the native forest (21 species) than in the reforested area (14 species). Recently, Moreira et al (2007b) found 25 AMF species three Araucaria ecosystems: a native forest (15 species), an Araucaria reforestation (13 species) and a burned Araucaria reforestation (13 species).…”
Section: Introductionmentioning
confidence: 99%
“…There are fungi that sporulate more, while others sporulate less, and others yet, do not sporulate or do so only during certain periods of the year (Table 1). Repeated sampling several times during the year could provide a more complete picture of this variability, as discussed in Moreira et al (2007b). Different AMF may have different carbon and other nutrient requirements for sporulation, and this may explain differing AMF phenologies (Violi et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Vários resultados demonstram que a colonização micorrízica e a eficiência micorrízica aumentam com adição de baixos teores de P (MOREIRA et al, 2007;MOREIRA-SOUZA;CARDOSO, 2002), ou pode ser reduzida em altos teores de P (SENA et al, 2004). Assim como o desenvolvimento das plantas também podem ser afetado pelo teor P no solo (COSTA et al, 2005).…”
Section: Introductionunclassified